A RARE CASE OF DUODENAL ECTROPIC CANCER (Vietnam Journal of Community Medicine, 2026)
Duodenal adenocarcinoma is a rare malignancy of the gastrointestinal tract, often diagnosed at a late stage due to nonspecific symptoms. While complete surgical resection offers the best long-term survival rate, recurrence rates remain significant, with the majority of recurrences occurring within the first two years. However, specific guidelines for optimal management of recurrence after surgery for duodenal adenocarcinoma are still lacking. Treatment guidelines are based on a small number of cases or on colorectal cancer treatment protocols, posing a significant challenge for clinicians in improving patient outcomes.This case report highlights a rare case of duodenal adenocarcinoma that underwent pancreaticoduodenectomy, lymph node dissection, and abdominal lymph node recurrence, aiming to describe a treatment strategy and contribute to the limited body of evidence for this rare and challenging condition.
Keywords: Adenocarcinoma, duodenal cancer, small intestine cancer